Effects of Lower Fishmeal With Hydrolyzed Fish Protein Powder on the Growth Performance and Intestinal Development of Juvenile Pearl Gentian Grouper (Epinephelus fuscoguttatus ♀ and Epinephelus lanceolatus ♂) - Vivian Hlordzi; Vivian Hlordzi; Junqing Wang; Tianbi Li; Zhiying Cui; Beiping Tan; Beiping Tan; Hongyu Liu; Hongyu Liu; Qihui Yang; Qihui Yang; Xiaohui Dong; et al. (Frontiers in Marine Science, 2022)
The effect of hydrolyzed fish protein powder (HFP) on the growth, intestinal development, gene mRNA expression, and enzyme activity in the intestine and liver of juvenile hybrid grouper (Epinephelus fuscoguttatus ♀ and Epinephelus lanceolatus ♂) was assessed after an 8-week feeding trial. Seven isonitrogenous (50%) and isolipidic (9%) diets were fed to hybrid grouper with 0% (CT), 1% (H1), 1.5% (H2), 2% (H3), 2.5% (H4), 3% (H5), and 4% (H6) HFP. No significant difference (p > 0.05) in weight gain rate (WGR), specific growth rate (SGR), feed conversion ratio (FCR), and survival rate (SR) was observed in all the groups. The crude protein content in the H6 group was significantly higher than in the other groups (p < 0.05). Intestinal lipase and trypsin activity were significantly higher in H3 and H5 groups (p < 0.05). In the serum, superoxide dismutase (SOD) activity was significantly higher in H5 and H6 groups, while malondialdehyde (MDA) activity was lower (p < 0.05) compared to other treatments. Insulin-like growth factor (IGF-I) and target of rapamycin (TOR) mRNA expression levels in the intestine and muscle were significantly higher in the H2 group and H1 group (p < 0.05), respectively. The most abundant intestinal bacteria found at the genus level are Acinetobacter, Vibrio, and Flavobacteriaceae. The villus was significantly longer in hybrid grouper fed with different levels of HFP compared to the control, and fish in the H2 group had thicker intestinal muscle compared to the other groups (p < 0.05). In conclusion, the addition of HFP to the low fishmeal (FM) diets of juvenile grouper improved the intestinal development and increased the levels of intestinal digestive enzymes.